Extract of Synedrella nodiflora (L) Gaertn exhibits antipsychotic properties in murine models of psychosis - Patrick Amoateng; Samuel Adjei; Dorcas Osei-safo; Kennedy K. E. Kukuia; Emelia Oppong Bekoe; Thomas K. Karikari; Samuel B. Kombian (BMC, 2017)
Abstract Background The hydro-ethanolic whole plant extract of Synedrella nodiflora (SNE) has demonstrated anticonvulsant, sedative and analgesic effects. Preliminary studies conducted in animals, SNE significantly decreased stereotypic behaviours suggesting antipsychotic potential. Coupled with the central nervous system depressant effects of SNE, we hypothesized that it may have utility in the management of psychosis. The present study therefore investigated the antipsychotic potential of the SNE in several murine models of psychosis. Method The primary central nervous system activities of SNE (30-3000 mg/kg, p.o) were investigated using the Irwin's test. The novelty-induced rearing, locomotion and stereotypy counts provoked by SNE (100-1000 mg/kg, p.o) were conducted using the open-field paradigm. The antipsychotic test models used in the screening of SNE (100-1000 mg/kg, p.o) included apomorphine-induced stereotypy, rearing, locomotion and cage climbing activities. The combined effects of a low dose of SNE (100 mg/kg) with various doses of haloperidol and chlorpromazine were analysed using the apomorphine-induced cage climbing and stereotypy, respectively. The ability of SNE to cause catalepsy in naïve mice as well as its effect on haloperidol-induced catalepsy was assessed. Results SNE showed acetylcholine-like and serotonin-like activities in the Irwin test, with sedation occurring at high doses. SNE significantly reduced the frequencies of novelty- and apomorphine-induced rearing and locomotion; stereotypy behaviour and the frequency and duration of apomorphine-induced cage climbing in mice. In all the tests performed, SNE was less potent than the reference drugs used (chlorpromazine and haloperidol). In addition, SNE potentiated the effects of haloperidol and chlorpromazine on apomorphine-induced cage climbing and stereotypy activities in mice. Conclusion SNE, while exhibiting antipsychotic properties itself, can also potentiate the antipsychotic effects of chlorpromazine and haloperidol.